MENUMBUHKAN MINAT DAN PEMAHAMAN NUMERASI MELALUI KEGIATAN FUN LEARNING DI BANJAR TEGALASAH DESA SANUR - Putu Catherine Tamira; Nabila Medianti Putri; Nurhasanah; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Math learning is often considered difficult and boring by children, so a more interesting approach is needed to increase their interest and understanding of numeracy concepts. In Banjar Tegalasah, Sanur Kaja Village, low learning motivation and lack of contextual educational media are the main challenges in learning mathematics. Responding to this challenge, Pendidikan Profesi Guru (PPG) Universitas PGRI Mahadewa Indonesia’s students implemented a Pengabdian kepada Masyarakat (PkM) program with the theme Fun Learning as part of the Leadership Project course which aims to make a real contribution to the community. Activities are carried out through several stages, namely socialization, media making training, application, assistance, and evaluation. Children were divided into small groups and invited to learn through games using three interactive educational media, namely Mathematics Ladder Snakes, KOPERTA (Multiplication and Addition Boxes), and Times Tables 1-11. The three media were designed to be simple yet effective in helping children understand numeracy concepts in a fun and collaborative way. The results of the activity showed a significant increase in learning motivation, understanding of basic math concepts, and children's confidence. In addition to benefiting the learners, this activity also strengthened students' social and leadership skills, and received positive responses from the community. The Fun Learning approach has proven effective in creating a more enjoyable, inclusive and relevant learning environment for children.